(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
In the context of an ageing population, the research and development of elderly women’s clothing has been widely discussed, and its clothing market has a good prospect. However, research on the design of T-shirts is mainly aimed at young people, and there is still a lack of research on the design of spring and autumn T-shirts specifically for elderly women. This paper conducts on-site research to understand the physical characteristics and clothing needs of elderly women and selects elderly obese women as the research object. The spring and autumn T-shirts are designed using a fake two-piece structural style combined with imitation woven, knitted fabric, and the rationality of the spring and autumn T-shirt design is verified through 3D virtual trial wear.